Peran Bimbingan Konseling Pada Siswa Inklusi di SMP Muhammadiyah 1 Kartasura - Rachmawati, Fatkur; Faisya Abrari Lutrinda; Yayuk Riana; Nurul Asma Khoiriyah; Ilham Nur Safitri; Rahayu Utami; Mahasri Shobabiya (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
This study aims to identify the role of Guidance and Counseling for inclusive children at SMP Muhammadiyah 1 Kartasura. Inclusion is a special education service for every child with special needs. Of course, it is one of the responsibilities of a guidance and counseling teacher at a school, especially at SMP Muhammadiyah 1 Kartasura, which is known that SMP Muhammadiyah 1 Kartasura is one of the schools that accepts inclusive students. From the data obtained, SMP Muhammadiyah 1 Kartasura has eight inclusive students, namely five students with a companion teacher for each student, and three students without a companion teacher. This study uses a qualitative methodology with a phenomenological approach taken from interviews with related BK teachers. Then the data is analyzed through interactive analysis. The results of this study are that BK teachers have an important role in helping inclusive students, including being the coordinator of each companion teacher, taking an approach to help inclusive students develop their potential, both in academic and social fields. The inhibiting factor for the role of guidance and counseling for inclusive students is the lack of assistance for some students due to parental disagreement. However, this is supported by inclusive students in this junior high school who show good development in socializing. Socialization efforts carried out by teachers regarding students with special needs (ABK) help non-inclusive students to understand and accept inclusive students, creating an inclusive and friendly environment for all students.